2021
DOI: 10.3389/fpubh.2021.797808
|View full text |Cite
|
Sign up to set email alerts
|

COVIDSAVIOR: A Novel Sensor-Fusion and Deep Learning Based Framework for Virus Outbreaks

Abstract: The presented deep learning and sensor-fusion based assistive technology (Smart Facemask and Thermal scanning kiosk) will protect the individual using auto face-mask detection and auto thermal scanning to detect the current body temperature. Furthermore, the presented system also facilitates a variety of notifications, such as an alarm, if an individual is not wearing a mask and detects thermal temperature beyond the standard body temperature threshold, such as 98.6°F (37°C). Design/methodology/approach—The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Similarly, in [101], a YOLOv4-based FMD is presented but lacks a thorough empirical evaluation. Authors in [115] developed a YOLOv4-based FMD and thermal scanning kiosk to (i) ease the classification of individuals wearing or not wearing masks and (ii) measure pedestrians' body temperatures using a temperature sensing unit. In [116], Gola et al have shown the superiority of YOLOv4 versus MobileNetv2, SSD and YOLOv3 in terms of FMD accuracy, whereas in [117] the authors verified the superiority of YOLOv4 over other variations, with a mAP value of 71.69%, and proposed YOLOv4-tiny for limited computational resources environments.…”
Section: One-stage Fmdmentioning
confidence: 99%
“…Similarly, in [101], a YOLOv4-based FMD is presented but lacks a thorough empirical evaluation. Authors in [115] developed a YOLOv4-based FMD and thermal scanning kiosk to (i) ease the classification of individuals wearing or not wearing masks and (ii) measure pedestrians' body temperatures using a temperature sensing unit. In [116], Gola et al have shown the superiority of YOLOv4 versus MobileNetv2, SSD and YOLOv3 in terms of FMD accuracy, whereas in [117] the authors verified the superiority of YOLOv4 over other variations, with a mAP value of 71.69%, and proposed YOLOv4-tiny for limited computational resources environments.…”
Section: One-stage Fmdmentioning
confidence: 99%
“…The germicidal effect of UV-C is already established with several germs and its use in the disinfecting of medical kits were also under process for COVID 19 virus ( Hashem et al, 2019 , Momattin et al, 2019 , Szeto et al, 2020 , Torres et al, 2020 ). Beside this applications, the different designs were also advanced for sanitization of currency, surface, documents, mask and PPE kit etc ( Pandya et al, 2021 , Ravi et al, 2021 , Tiwary et al, 2021 ). However, these developed design technologies are able to decontaminate the assets up to certain extents but few scientific facts must be considered for effective application.…”
Section: Technical Aspects Of Uv Based Covid 19 Dispersion Mitigation...mentioning
confidence: 99%
“…The portrayal of substantial depressive cues from the literature is one of the most challenging tasks. Previous research has discovered that an automated textual analysis of depressive symptoms can be used in, for example, detecting disrespectful or depressing phrases or sentences in conversations or blog postings, as well as sentiment recovery from suicide notes [1,[15][16][17]. The categorization of shared blog posts is critical to examine to save the lives of any desperate individuals.…”
Section: Introductionmentioning
confidence: 99%